2011
DOI: 10.1051/0004-6361/201015384
|View full text |Cite
|
Sign up to set email alerts
|

The excitation of 5-min oscillations in the solar corona

Abstract: Aims. We aim to study excitation of the observed ∼5-min oscillations in the solar corona by localized pulses that are launched in the photosphere. Methods. We solve the full set of nonlinear one-dimensional Euler equations numerically for the velocity pulse propagating in the solar atmosphere that is determined by the realistic temperature profile. Results. Numerical simulations show that an initial velocity pulse quickly steepens into a leading shock, while the nonlinear wake in the chromosphere leads to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
(35 reference statements)
2
10
0
Order By: Relevance
“…This mechanism has been identified in many observational and theoretical studies (e.g. De Moortel, Ireland, and Walsh, 2000;Marsh et al, 2003;De Pontieu, Erdélyi, and James, 2004;De Pontieu, Erdélyi, and De Moortel, 2005;Didkovsky et al, 2011;Zaqarashvili et al, 2011). Hence we can propose that the leakage of oscillation modes from the layers below the corona is also an important driving mechanism for the generation of the observed QFP wave in the low corona, in line with our previous results (Shen and Liu, 2012a).…”
Section: The Generation Of the Qfp Wavesupporting
confidence: 91%
“…This mechanism has been identified in many observational and theoretical studies (e.g. De Moortel, Ireland, and Walsh, 2000;Marsh et al, 2003;De Pontieu, Erdélyi, and James, 2004;De Pontieu, Erdélyi, and De Moortel, 2005;Didkovsky et al, 2011;Zaqarashvili et al, 2011). Hence we can propose that the leakage of oscillation modes from the layers below the corona is also an important driving mechanism for the generation of the observed QFP wave in the low corona, in line with our previous results (Shen and Liu, 2012a).…”
Section: The Generation Of the Qfp Wavesupporting
confidence: 91%
“…However, Murawski and Zaqarashvili (2010) and Zaqarashvili et al (2011) suggested that the observed periodicity in the solar corona is caused by quasi-periodic rebound shocks, originating from nonlinear wakes in the stratified atmosphere. Here we have developed the same idea and solved the ideal MHD equations in the case of a realistic temperature profile.…”
Section: Discussionmentioning
confidence: 99%
“…The amplitude of oscillations is stronger at greater height, but oscillations decay rapidly at each height as time progresses. and acoustic oscillations (Murawski & Zaqarashvili 2010;Zaqarashvili et al 2011) near the acoustic cut-off period of the chromosphere. In a similar way, the recurrent shocks may cause the density oscillations in the higher corona with the coronal acoustic cut-off period, which is much greater than that of the chromosphere.…”
Section: Oscillation Of Coronal Plasma At Acoustic Cut-off Frequency mentioning
confidence: 99%